\[\boxed{\text{718\ (718).\ }\text{Еуроки\ -\ ДЗ\ без\ мороки}}\]
\[1)\ 15\text{cx} + 2\text{cy} - \text{cxy} - 30c =\]
\[= 15c(x - 2) - \text{cy}(x - 2) =\]
\[= (x - 2)\left( 15c - \text{cy} \right) =\]
\[= c \cdot (15 - y)(x - 2)\]
\[2)\ 35a² - 42ab + 10a^{2}b - 12ab^{2} =\]
\[= 5a^{2}(7 + 2b) - 6ab(7 + 2b) =\]
\[= (7 + 2b)\left( 5a^{2} - 6ab \right) =\]
\[= a \cdot (7 + 2b)(5a - 6b)\]
\[3)\ x^{3} + x^{2}y + x^{2} + xy =\]
\[= x^{2}(x + y) + x(x + y) =\]
\[= (x + y)\left( x^{2} + x \right) =\]
\[= x \cdot (x + y)(x + 1)\]
\[4)\ mn^{4} - n^{4} + mn^{3} - n^{3} =\]
\[= n^{4}(m - 1) + n^{3}(m - 1) =\]
\[= (m - 1)\left( n^{4} + n^{3} \right) =\]
\[= n^{3}(m - 1)(n + 1)\]
\[\boxed{\text{718.\ }\text{Еуроки\ -\ ДЗ\ без\ мороки}}\]
\[Пусть\ даны\ последовательные\ \]
\[натуральные\ числа\ \]
\[(с\ меньшего):\ \ \ \]
\[n,\ \ \ n + 1,\ \ \ n + 2,\ \ \ n + 3.\]
\[(n + 1)^{2} + (n + 3)^{2} - сумма\ \]
\[квадратов\ второго\ и\ \]
\[четвертого\ чисел\ на\ 82\ \]
\[больше,\ чем\]
\[n^{2} + (n + 2)^{2} - сумма\ \]
\[квадратов\ первого\ и\ третьего\ \]
\[чисел.\]
\[Составим\ уравнение:\]
\[4n = 76\]
\[n = 19 - первое\ число.\]
\[19,\ 20,\ 21,\ 22 - искомые\ числа.\]
\[Ответ:19,\ 20,\ 21,\ 22.\]